2022
DOI: 10.3991/ijim.v16i13.30909
|View full text |Cite
|
Sign up to set email alerts
|

The Capabilities, Challenges, and Resilience of Digital Learning as a Tool for Education During the COVID-19

Abstract: The current study's objective examines contemporary advancements in learning utilizing digital technology for educational purposes during the recent pandemic outbreak. The study analysed the challenges, capabilities, and resilience of these digital learning environments and the future of digital learning. The PRISM statement is used to select records and assess the final 37 studies for the current investigation. According to the findings, the COVID-19 pandemic posed a significant challenge to educational insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Online learning, though not easy to adapt to initially, proved to be effective during the hardest times (Rahayu and Wirza, 2020;Mushtaha et al, 2022). Numerous studies have proven that online tools can effectively simulate in-person instructions (Yasir et al, 2022). Roque-Hernández et al (2023) reported that, owing to the interactive features offered by online learning environments, students have more positive experiences and engagement during classes, even though the classes were held online.…”
Section: Introductionmentioning
confidence: 99%
“…Online learning, though not easy to adapt to initially, proved to be effective during the hardest times (Rahayu and Wirza, 2020;Mushtaha et al, 2022). Numerous studies have proven that online tools can effectively simulate in-person instructions (Yasir et al, 2022). Roque-Hernández et al (2023) reported that, owing to the interactive features offered by online learning environments, students have more positive experiences and engagement during classes, even though the classes were held online.…”
Section: Introductionmentioning
confidence: 99%
“…On the surface, this has sparked a wave of educational innovation. Institutions worldwide have welcomed increased flexibility, providing virtual and actual courses [2]. However, before recent technological advancements, the learner-centred education system was a step from the old tutor-centred education system [3].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the recent emphasis on Industry 4.0 still lacks a specific, widely recognised definition (Hofmann & Rüsch, 2017). The SCM literature shows a growing interest in exploring Industry 4.0 (Yasir et al, 2022). According to (Sikandar et al, 2022), Industry 4.0 solutions boost overall operational performance by allowing faster and more cost-effective responses.…”
Section: Introductionmentioning
confidence: 99%